Kepentingan Indonesia Menjadikan Palembang Sebagai Co-Host City Dalam Asian Games 2018 - Dewi, Putu Amelia; Dharmiasih, D.A. Wiwik; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2020)
ABSTRACT                 This research aims to describe the interests of Indonesia in the Asian Games 2018 by using qualitative research methods. Indonesia established Palembang as the co-host city Asian Games 2018 to accompany DKI Jakarta. Palembang has various experiences in organizing sports events, tourism potential, and sports facilities. Palembang is projected to become a sports tourism destination to attract tourist visits. The researcher uses two main concepts, Sports in IR and National Interests in order to answer Indonesia's interests in Asian Games 2018. This research perceives that Indonesia has economic interests through established Palembang as the co-host city of Asian Games 2018. Keywords: Indonesia, Palembang, Asian Games 2018, National Interests